CLIL APPROACH TO LEGAL ENGLISH COURSES: ANALYSIS OF PRACTICE AND EXPERIENCE - Grigorievna Vyushkina, Elena (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*289.15px); top: calc(var(--scale-factor)*75.38px); font-size: calc(var(--scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.14338);" role="presentation">http://dx.doi.org/10.1515/sm-2017-0007 The EU consistent policy on languages promotes new language teaching methods and encourages pedagogical experiments at all levels of education, Content and Language Integrated Learning (CLIL) being one of language education innovations. Over the past twenty years CLIL proved to be an effective method in foreign language acquisition and there is considerable evidence of successful CLIL implementation in secondary schools in many European countries. Speaking about foreign languages in higher education, it is necessary to note that abbreviation EMI – English as a Medium of Instruction – is mentioned much more often than CLIL. One of the reasons for lower CLIL implementation at a tertiary level is the complexity of subject contents taught at universities. Furthermore, if a student’s major is law, the issue becomes more challenging because of the differences in common law and civil law systems. However, one of lawyer’s professional competences directly connected with language learning is a communicative competence. Such spheres of lawyer’s activity as client counseling, negotiation, and mediation rely heavily on listening, paraphrasing, reframing, summarising, and skills of question formation regardless of what legal system a lawyer belongs to. These so-called soft skills can be developed within a foreign language course but it seems more rational to master them through a professional medium. Therefore, law teachers should be engaged in designing a substantive part of course materials, while language teachers are to be in charge of communicative competence development. The present study aims at analyzing the practice and experience in designing and implementing an original optional course “Client Consultation in English”. This course can serve as an illustration of a CLIL Legal English course and its structure can be used as an example to follow while designing similar courses.